La Venus de cobre - Davis, Lindsey (Davis, Lindsey. Falco series., 2010)
In 70 A.D. in ancient Rome, no one is a saint. Or so thinks Marcus Didius Falco, a private investigator first introduced in the award-winning SILVER PIGS, who's trying to prevent a murder before it happens. When every man a woman marries dies, Falco knows there's smoke and fire--and he'll stop at nothing to untangle the Gordion knot that proves it.